Fear of the human “super predator” far exceeds the fear of large carnivores in a model mesocarnivore - Clinchy, M; Zanette, L; Roberts, D; Suraci, J; Buesching, C; Newman, C; Macdonald, D (Oxford University Press, 2016)
The fear (perceived predation risk) large carnivores inspire in mesocarnivores can affect ecosystem structure and function, and loss of the “landscape of fear” large carnivores create adds to concerns regarding the worldwide loss of large carnivores. Fear of humans has been proposed to act as a substitute but new research identifies humans as a “super predator” globally far more lethal to mesocarnivores, and thus presumably far more frightening. Although much of the world now consists of human-dominated landscapes there remains relatively little research regarding how behavioral responses to humans affecttrophic networks, to the extent that no study has yet experimentally tested the relative fearfulness mesocarnivores demonstrate in reaction to humans versus nonhuman predators. Badgers (Meles meles) in Britain are a model mesocarnivore insofar as they no longer need fear native large carnivores (bears, Ursus arctos; wolves, Canis lupus) and now perhaps fear humans more. We tested the fearfulness badgers demonstrated to audio playbacks of extant (dog) andextinct (bear and wolf) large carnivores, and humans, by assaying the suppression of foragingbehavior. Hearing humans affected all of: latency to feed, vigilance, foraging time, number of feeding visits, and number of badgers feeding. Hearing dogs and bears had far lesser effects on latency to feed, and hearing wolves had no effects. Our results indicate fear of humans evidently cannot substitute for the fear large carnivores inspire in mesocarnivores because humansare perceived as far more frightening, which we discuss in light of the recovery of large carnivores in human-dominated landscapes.